(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
This study aims to evaluate the addition of butterfly pea flower extract as a natural antioxidant source in Skim Milk with Egg Yolk on the quality of Boer goat spermatozoa. The study used a Randomized Block Design (RBD) with five treatments and four replicates, and the data were further analyzed using Duncan’s test. The treatments consisted of sperm added to skim milk (control, P0) and to skim milk with egg yolk, with the addition of butterfly pea flower extract at various doses (P1 = 2 mL, P2 = 4 mL, P3 = 6 mL, P4 = 8 mL). The parameters observed were motility, viability, abnormality, and intact plasma membrane. The results showed that the addition of butterfly pea flower extract had a significant effect (p<0.05) on all parameters observed. Increasing the treatment dose produced a consistent biological response, with treatment P4 (8 mL) being the best treatment. Based on the results, the antioxidant content of butterfly pea flower extract protected the membrane and structure of spermatozoa from oxidative damage during storage. The study concluded that the addition of butterfly pea flower extract has the potential to be used as a supplement in semen diluents to improve the stability and quality of Boer goat semen.